Type D Personality Is Associated with Poorer Quality of Life in Patients with Chronic Spontaneous Urticaria: A Cross-sectional Study - Manuel Sánchez-Díaz; Maria-Carmen S; Alejandro Molina-Leyva; Salvador Arias-Santiago (Medical Journals Sweden, 2022)
Type D personality (TDp) is a stable personality type that has been associated with poor quality of life in the general population and in patients with a variety of diseases, such as cancer, cardiac diseases, and dermatological diseases (e.g. psoriasis). To date, the potential association between chronic spontaneous urticaria and TDp has not been studied. The aim of this study is to analyse the impact of TDp on patients with chronic spontaneous urticaria, regarding mood disturbances, quality of life, sexuality, and sleep disturbances. A cross-sectional study including 75 patients with chronic spontaneous urticaria was performed. Data on socio- demographic variables and disease activity, quality of life, sleep, sexual dysfunction, anxiety, depression and TDp were collected using validated questionnaires. TDp was present in 28% (21/75) of the patients. Although TDp was not related to worse disease control, the presence of anxiety and depression was higher in patients with TDp. Regarding quality of life, TDp was associated with poorer quality of life and higher frequency of sleep disturbances. Prevalence of TDp in patients with chronic spontaneous urticaria is similar to that in the general population. It is associated with mood status disturbances and worse quality of life regardless of disease severity, especially in the emotional and psychological domains. This group of patients could benefit from additional psychological support as a complement to their medical treatment.